Design of a powered ankle-foot prosthesis with an adjustable stiffness toe joint. (18th May 2020) - She, Haotian; Zhu, Jinying; Tian, Ye; Wang, Yanchao; Huang, Qiang
ABSTRACT: This paper proposes a powered ankle-foot prosthesis called PANTOE II, which includes an ankle and a segmented foot with a toe joint. The ankle and toe joints are both driven by series elastic actuators, which can reduce the required velocity and energy consumption of the actuators. The mechanical design of the ankle and toe joints makes the prosthesis more compact. In addition, PANTOE II employs a more human-like foot, which includes the heel, the mid foot, and the toe. Both the heel and the toe are made of leaf springs, and the mid foot is used to install the transmission mechanisms. The finite state control strategy is used for controlling the prosthesis. To evaluate the basic performance of PANTOE II, experiments are conducted on a subject with a transtibial amputation. Wearing PANTOE II, the amputee feels more comfortable and presents more symmetrical walking gaits. GRAPHICAL ABSTRACT: